Clinical pathological evaluation and risk factors of oral cancer cases of east coast of peninsular Malaysia - Zain , R.B.; Samsudin, A. R.; Farini, M. S.; Azlina, A.; Rushdan, I.; Manoharan, M. (Elsevier, 2005)
Introduction: Oral cancer is one of the common cancers m Malaysia. Tile population of east coast of Peninsular Malaysia has a different hfestyle and Malay is the predominant race. Oral cancer research in this area started since the Malaysian National Oral Cancer group was established. The am: of this study is to evaluate the clinical pathological findings and to investigate the role of tobacco smoking, alcohol consurnption and betel quid chewing as tile risk factors among oral cancer cases m east coast of peninsular Malaysia.Materials and Methods: Fifty case records of only treated/operated cases of patients with oral cancer between 1994-2003 m Hospital Umversiti Sams Malaysm were reviewed. This study is based on questio:matre developed by the Malaysian National Oral Cancer group. Tile data analysed includes personal reformation and clinical pathological findings. Results: Patients' age range was between 27-97 years old. The male to female ratio was 1.4:1. Malays ethic group has the highest incidence of oral cancer (n=46). Out of 50 cases, 80% were new cases and 66% was squamous cell carcinoma of the oral mucosa. Data revealed 12 different sites of lesions and the highest frequency was on buccal mucosa (30%) with 75% neck node involvement while 12% of the patients have two s:tes of les:oias. D:stant metastams occurred m 76.9% of the cases. Tobacco smoking was found to be the predorrm:ant risk factor (54%) wtnle 24% of pat:ents were found to be qurd chewer. Only 8% ofpafients consumed alcohol. The remaining14% patients do not admit any of the risk factors and the author would contribute their etiolo~ to viruses. Conclusion: The most common site of oral cancer was buccal mucosa with 75% neck node involvement. Presence of distant metastasis can be witnessed on most cases. More than half cases were new cases. Tobacco smokings exceed betel nut chewing as a probable risk factor among the subjects.